2021
DOI: 10.1186/s13578-021-00726-x
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy deficiency in neurodevelopmental disorders

Abstract: Autophagy is a cell self-digestion pathway through lysosome and plays a critical role in maintaining cellular homeostasis and cytoprotection. Characterization of autophagy related genes in cell and animal models reveals diverse physiological functions of autophagy in various cell types and tissues. In central nervous system, by recycling injured organelles and misfolded protein complexes or aggregates, autophagy is integrated into synaptic functions of neurons and subjected to distinct regulation in presynapti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 86 publications
2
13
0
Order By: Relevance
“…In addition, YG mice display a progressive reduction in muscular strength, motor functions and abilities, and learning performance [157] . Such deficits are associated with age-dependent cognitive decline, autophagic dysfunction, and progressive dendritic spine loss [125] , mirroring some of the crucial features reported in patients [158] ( Fig. 1 ).…”
Section: The 682 Yenpty 687 -Me...supporting
confidence: 53%
“…In addition, YG mice display a progressive reduction in muscular strength, motor functions and abilities, and learning performance [157] . Such deficits are associated with age-dependent cognitive decline, autophagic dysfunction, and progressive dendritic spine loss [125] , mirroring some of the crucial features reported in patients [158] ( Fig. 1 ).…”
Section: The 682 Yenpty 687 -Me...supporting
confidence: 53%
“…Recently, a functional enrichment analysis obtained from a cross-ancestry genome-wide association study found a group of enriched genes involved in membrane trafficking, Golgi-to-ER trafficking, and autophagy within ALS-associated loci [ 82 ]. This result further tethers ALS to MAMs modulation of autophagic/mitophagic processes, already described with other ALS experimental paradigms [ 83 ].…”
Section: Involvement Of Fals-associated Proteins In Mitochondrial Dys...supporting
confidence: 72%
“…It has also been shown that bi-allelic null mutations in p62 present with early-onset neurodegenerative disorders (Haack et al, 2016;Muto et al, 2018). Specifically, it resulted in a dramatic increase of lactate dehydrogenase A (LDHA) expression, which correlated with deficient neurodifferentiation due to the inability to upregulate genes important for OXPHOS (Calvo-Garrido et al, 2019), a phenotype rescuable by N-acetylcysteine, suggesting a role of p62 in oxygen sensing or ROS management and implying the role of autophagy in brain-related disorders (Lee et al, 2013;Deng et al, 2021). It is known that under oxidative stress p62 stabilizes Nrf2 (Jain et al, 2010;Komatsu et al, 2010).…”
Section: Mitochondrial Physiology Autophagy and Epigenetics Interplay...mentioning
confidence: 99%